A systematic study of carbon fibre surface grafting via in situ diazonium generation for improved interfacial shear strength in epoxy matrix composites. (30th October 2015) - Beggs, Kathleen M.; Servinis, Linden; Gengenbach, Thomas R.; Huson, Mickey G.; Fox, Bronwyn L.; Henderson, Luke C.
Abstract: A recently established means of surface functionalization of unsized carbon fibres for enhanced compatibility with epoxy resins was optimised and evaluated using interfacial shear stress measurements. Interfacial adhesion has a strong influence on the bulk mechanical properties of composite materials. In this work we report on the optimisation of our aryl diazo-grafting methodology via a series of reagent concentration studies. The fibres functionalised at each concentration are characterised physically (tensile strength, modulus, coefficient of friction, and via AFM), and chemically (XPS). The interfacial shear strength (IFSS) of all treated fibres was determined via the single fibre fragmentation test, using the Kelly–Tyson model. Large increases in IFSS for all concentrations (28–47%) relative to control fibres were observed. We show that halving the reagent concentration increased the coefficient of friction of the fibre and the interfacial shear strength of the composite while resulting in no loss of the key performance characteristics in the treated fibre.